The impact of member participation as owners and customers on equity capital efficiency in the Pasir Jambu cooperative - Wulandari, Latifah; Sarusu, Armansyah M.; Gorib, Ridwan Ismail (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the effect of member participation as owners and customers on the efficiency of equity capital in the Pasir Jambu Cooperative. Member participation as owners and customers is an important factor that influences the cooperative's ability to manage capital efficiently, which in turn has an impact on the sustainability and performance of the cooperative. The research method used is quantitative, with primary data collected through questionnaires distributed to members of the Pasir Jambu Cooperative. The data analysis technique uses multiple linear regression to identify the relationship between member participation as owners and customers on equity capital efficiency. The results of the study indicate that member participation as owners has a significant effect on equity capital efficiency, while participation as customers shows a moderate effect. The implications of this study indicate that increasing member participation both as owners and customers can strengthen the equity efficiency of the Cooperative, thereby increasing the competitiveness of the cooperative in a competitive market